Bacteriocin KvarM versus conventional antibiotics: comparative effectiveness in treating Klebsiella pneumoniae infections in murine intestinal models - Indre Karaliute; Deimante Tilinde; Rima Ramonaite; Rokas Lukosevicius; Darja Nikitina; Jurga Bernatoniene; Irma Kuliaviene; Irena Valantiene; Dalius Petrauskas; Vilma Zigmantaite; Vilma Zigmantaite; Audrius Misiunas; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionThe rapid emergence of multidrug-resistant bacterial species poses a critical threat by reducing the efficacy of antibiotics and complicating infection treatment. Bacteriocins, such as klebicin KvarM, have emerged as promising alternatives to traditional antibiotics due to their targeted antimicrobial activity. In this study, we evaluated the therapeutic potential of Eudragit-coated klebicin KvarM in a mouse model of Klebsiella pneumoniae intestinal colonization, assessing both its antimicrobial effectiveness and impact on commensal gut microbiota.MethodsAntimicrobial activity of KvarM in comparison to conventional antibiotic therapy with ciprofloxacin was tested in murine models for K. pneumoniae gastrointestinal (GI) tract infection. The haemolysin gene (khe) was chosen as the qualitative marker for Klebsiella genus identification, and 16S rRNA gene sequencing of V1-V2 hypervariable region was performed for analyses of gut microbiota.ResultsOur results demonstrated that KvarM was highly effective in reducing K. pneumoniae colonization, showing the same efficacy as ciprofloxacin. Following K. pneumoniae inoculation, administration of KvarM resulted in a significant reduction in bacterial load indicating a 99% effectiveness. Furthermore, microbiome analysis of the gut microbiota revealed that KvarM therapy showed no significant changes in microbial composition compared with commensal microbiota composition, whereas administration of ciprofloxacin led to a significant decrease in microbial diversity.DiscussionThese findings demonstrate that klebicin KvarM therapy is highly effective for treating intestinal K. pneumoniae infections and it does not affect the integrity of the gut microbiota.